An evaluation of merocel and neosporin impregnated ribbon gauze packs in patients following nasal surgery: a prospective randomised trial - Joshi, RR; Nepal, A; Chhetri, S Thapa; Bhandary, S; Panta, TB; Regmi, D (Health Renaissance, 2012)
Background: Packs are placed following nasal surgeries to arrest haemorrhage, to prevent septal haematoma and synechie formation. Despite Merocel, a tampon constructed from a foam polymer of hydroxylated polyvinyl acetate, which is less abrasive and hence associated with the less pain, we still use Neosporine Impregnated Ribbon Gauze (NIRG). Objective: To compare Merocel and the Neosporine Impregnated Ribbon gauze (NIRG) packs in regards to the post-operative pain levels caused by them and their ability to prevent haemorrhage, crusting and synechie. Methods: The nose was packed after surgery either with the Merocel pack or Neosporin Impregnated Ribbon Gauze (NIRG) according to the randomisation. The pain score was noted on the Visual analog score while packs were in situ and again immediately after the pack removal. The haemorrhage, crusting and synechie were noted if present. Results: Among 106 patients, 61 were male and 45 were female. In Merocel group there were 51 patients and in NIRG group 55. The mean pain score for merocel was 4.15 while in situ and 3.66 immediately after removal where as mean pain score for NIRG was 6 while in situ and 3.78 immediately after removals. Post-operative crusting and synechie were seen relatively more in NIRG pack group. Conclusion: Merocel is superior in terms of both patient comfort and pain. DOI: http://dx.doi.org/10.3126/hren.v10i1.6004 HREN 2012; 10(1): 30-34